Analysis of RC Quadcopter RCS Estimation in indoor and Outdoor Environments with L-Band Primary Surveillance Radar - Wipassorn Vinicchayakul; Chinwat Poorahong; Korawit Mahakunwong; Jateslid Singsathien; Nuttakorn Trirattanawananon; Monchai Chamchoy (My University, 2022)
This research is to study and analyze quadcopter radar cross section (RCS) in indoor and outdoor environments of L-Band primary surveillance radar (PSR), working at 1215–1350 MHz, using vector network analyzers. The research is divided into two parts, the first one is the RCS test of the quadcopter in an indoor environment compared to an outdoor environment. The second part is the RCS test of the quadcopter in an indoor environment while the quadcopter is flying in the air compared to the quadcopter mounted on a stand as in the first test. The results showed that the RCS of the quadcopter in both environments responded to the structure of the quadcopter in the same way, but the RCS of quadcopter in indoor environment has higher RCS anomality oscillation compared to the RCS of quadcopter in outdoor environment. In addition, the quadcopter that is flying in the air compared to the quadcopter mounted on a stand has found that the majority of the quadcopter’ RCS is similar.
Keywords: UAV Applications and Optimization; Radar Systems and Signal Processing; Antenna Design and Optimization